Legal Aspects of the Quinoa Imports Into the EU - Lazíková Jarmila; Takáč Ivan; Rendón Schneir Eric; Rumanovská Ľubica (EU agrarian Law)
Quinoa is known in the EU as superfood due to the high level of protein, fibre, micronutrients, and amino acids. It is come from South America; however, quinoa is currently grown in various parts of the world. Nevertheless, the domestic continent, especially countries such as Peru and Bolivia, is one of the world’s largest producers and exporters of quinoa. One third of Peru’s quinoa production is imported to European Union. Despite the conclusion of an agreement with Peru and Bolivia that eliminated quinoa tariffs, there are many legal regulations of the EU that affects import of quinoa into the EU countries including the food safety and quality, food labelling, organic labels and nutrition and health claims, food packaging and shipment. The article deals with the most important EU legal norms of quinoa imports that must be complied with when importing quinoa.